2022
DOI: 10.1038/s41420-022-00864-2
|View full text |Cite
|
Sign up to set email alerts
|

Golgi phosphoprotein 3 induces autophagy and epithelial–mesenchymal transition to promote metastasis in colon cancer

Abstract: In this study, we aimed to investigate whether and how Golgi phosphoprotein 3 (GOLPH3) facilitates colon cancer metastasis via the regulation of autophagy and epithelial–mesenchymal transition (EMT). The role GOLPH3 plays in colon cancer metastasis was analyzed using western blotting, immunohistochemistry, transwell, wound-healing, and zebrafish assays. Autophagy and EMT were assessed via RNA-sequencing (RNA-seq) analysis, mRFP-GFP-LC3 reporter assays, and their related markers. Significant associations were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Mounting evidence has demonstrated that increased cancer cell invasion is associated with EMT-like process. [35][36][37][38] Interestingly, we found that overexpression of SNRPA promoted a transformation from the expression of epithelial markers to mesenchymal markers, indicating that SNRPA promoted the EMT-like process in HCC cells. Herein, we further explored the potential mechanism of SNRPA in the EMTlike process of HCC cells.…”
Section: Discussionmentioning
confidence: 77%
“…Mounting evidence has demonstrated that increased cancer cell invasion is associated with EMT-like process. [35][36][37][38] Interestingly, we found that overexpression of SNRPA promoted a transformation from the expression of epithelial markers to mesenchymal markers, indicating that SNRPA promoted the EMT-like process in HCC cells. Herein, we further explored the potential mechanism of SNRPA in the EMTlike process of HCC cells.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that the PI3K pathway is involved in the migration, invasion and EMT of HCC cells ( 39 , 46 ). The effects of different concentrations of DHW-208 on the migration and invasion of Hep3B and Bel7402 cells were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because GOLPH3 is required to support Golgi apparatus integrity and the latter has been reported to inhibit autophagy [ 27 ] we expected induction of autophagy upon inactivation of dGOLPH3. While GOLPH3 has been recently involved in regulation of autophagy in human cultured cells and in a few tumor contexts [ 38 , 59 , 60 ], its role in the process is not understood. Our findings indicating that autophagy is supported by dGOLPH3 at the step of transcriptional induction of autophagy regulated by Mitf/TEB, suggest that loss of dGOLPH3 might inhibit translocation of TFEB from lysosomes to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the Drosophila GOLPH3 (dGOLPH3) protein, encoded by the sauron (sau) locus, accumulates at the cleavage site during telophase and acts as a key molecule during cytokinesis to couple PI(4)P signaling and membrane remodeling with actomyosin ring dynamics [ 35 37 ]. Frequent overexpression of GOLPH3 has been correlated with poor prognosis in multiple cancer types including breast cancer, colon cancer and glioblastoma [ 33 , 38 , 39 ]. The oncogenic activity of human GOLPH3 has been correlated with enhanced activity of growth factor-induced mTOR signaling [ 39 ].…”
Section: Introductionmentioning
confidence: 99%